Correlates of reactive hyperemic index in men and postmenopausal women. (December 2013) - Carnovale, Valérie; Paradis, Marie-Eve; Gigleux, Iris; Ramprasath, Vanu R; Couture, Patrick; Jones, Peter J; Lamarche, Benoît; Couillard, Charles
The aim of the present study was to investigate the differences in digital reactive hyperemic index (RHI) in men and postmenopausal women. We investigated the differences in and correlates of RHI, measured by peripheral artery tonometry (PAT), in a group of 82 men (mean age ± SD: 55.6 ± 8.2 years; body mass index: 29.0 ± 4.2 kg/m 2 ) and 125 postmenopausal women (58.9 ± 5.2 years; 27.7 ± 4.1 kg/m 2 ). We also examined fRHI values (natural log of the PAT ratio of the 90–120 seconds post-occlusion interval) and augmentation index (AIx) as a measure of arterial stiffness. We found that RHI, fRHI and AIx were significantly lower in men compared to postmenopausal women ( p <0.0001). We also found that fRHI values were significantly lower in individuals with (MetS+) versus without (MetS–) the metabolic syndrome (MetS). Endothelial inflammation was present in MetS+ subjects as indicated by increased plasma soluble intercellular adhesion molecule-1 (sICAM-1) ( p <0.001) and E-selectin ( p =0.0519) concentrations compared to MetS– individuals. No significant difference was found in RHI or AIx between MetS+ versus MetS– individuals. In summary, our study reveals that men have an impairment of endothelial function, assessed by digital PAT, compared to postmenopausal women. Furthermore, we show that the presence of the MetS is characterized by endothelial dysfunction, as suggested by lower fRHI, as well as by endothelial inflammation, which likely contributes to the increased cardiovascular disease risk associated with the MetS.ClinicalTrials.gov Identifier: NCT01085019